The Relationship Between Morphological Awareness and Reading Comprehension Among Chinese Children - Xie, Ruibo; Zhang, Jie; Wu, Xinchun; Nguyen, Thi Phuong (Frontiers in Psychology, 2019)
The present study examined the developmental relationship between morphological awareness and reading comprehension, using a 1-year longitudinal study with a sample of 439 Chinese-speaking students in Grades 1, 3, and 5, respectively. Children’s text reading and three components of morphological awareness: homophone awareness, homograph awareness and compounding awareness were measured. After controlling for word reading, vocabulary knowledge, IQ, rapid automatized naming and phonological awareness measured at the initial level, the structural equation modeling results indicated that children’s compounding awareness made a significant direct contribution to reading comprehension only from Grade 5 to 6. Children’s reading comprehension also made a unique contribution to compounding awareness from Grade 5 to 6. Thus a reciprocal relationship between compounding awareness and reading comprehension was found for Grade 5 to 6. Reading comprehension in Grades 3 predicted homophone awareness in Grades 4 was marginal significance, but initial homophone awareness did not predict later reading comprehension across grades. Furthermore, there no unique connection between homograph awareness and reading comprehension across grades. These findings suggest a dynamic relationship between different aspects of morphological awareness and reading comprehension in Chinese-speaking children across elementary school years.